Peningkatan Kemampuan Mahasiswa Dalam Materi Termodinamika Dengan Metode Tugas Mandiri dan Eksperimen Pada Program Studi Tadris IPA Fisika UIN Imam Bonjol Padang - Asrar, Allan (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2020)
The purpose of this study was to determine the improvement of student ability through independent tasks and experiment methods in the Science Tadris Study Program of Physics, UIN Imam Bonjol "with the concepts of temperature and the first law of thermodynamics and heat capacity. The results showed that the value of the independent assignment on the temperature concept material with an average pre-test score of 39.03 and an average post-test score of 60.32. From the results of the prestest and posttest, the percentage increase in value was 55.45%. In the first law material of thermodynamics and heat capacity, the learning process in the first law material of thermodynamics is an independent task coupled with experiments. The results obtained are the value of independent assignments on the subject of law I thermodynamics and heat capacity with an average pre-test value of 55.15 and an average posttest score of 77.39. From the results of the prestest and posttest, the percentage increase in value was 41.45%. Furthermore, the experimental value with the material of the first law of thermodynamics obtained an average experimental value at the pretest of 53.04 and the average result of the posttest was 74.04. The percentage increase between the pretest and poststest values was 40.79%. Based on the results of the study, it was concluded that the posttest average was higher than the average prestest so it could be concluded that through the independent assignment method and experimentation it could improve students' abilities on the concept of temperature, first law of thermodynamics and heat capacity.